Factory - Darley, Gillian, 1947- (London : Reaktion, 2003)
Gillian Darley's study is a social, cultural and architectural history of the factory from its beginnings to the present day. The book includes several images, some of which are in colour.
Industriële archeologie (rubricering Patrick Viaene)
Includes bibliographical references and index.
Keywords: Factories -- History; Factories -- Social aspects; Factories -- Design and construction; Usines -- Histoire; Usines -- Aspect social; Usines -- Conception et construction; Fabrieksgebouwen